2021
DOI: 10.3390/nano11040923
|View full text |Cite
|
Sign up to set email alerts
|

Beam Theory of Thermal–Electro-Mechanical Coupling for Single-Wall Carbon Nanotubes

Abstract: The potential application field of single-walled carbon nanotubes (SWCNTs) is immense, due to their remarkable mechanical and electrical properties. However, their mechanical properties under combined physical fields have not attracted researchers’ attention. For the first time, the present paper proposes beam theory to model SWCNTs’ mechanical properties under combined temperature and electrostatic fields. Unlike the classical Bernoulli–Euler beam model, this new model has independent extensional stiffness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, researchers have rarely paid attention to the material nonlinearity of nanobeams [22]. Nanobeam's nonlinearity in the thermal-electromechanical coupling also is a required eld [23][24]. Researchers have usually modi ed the classical continuum mechanics to capture the small-scale effect through three different paths: the nonlocal stress gradient model 1 − e 0 a 2 ∇ 2 σ ij = σ ij [7], the strain gradient model σ ij = 1 − e 0 a 2 ∇ 2 ε ij [9,[25][26], and the surface stress model [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have rarely paid attention to the material nonlinearity of nanobeams [22]. Nanobeam's nonlinearity in the thermal-electromechanical coupling also is a required eld [23][24]. Researchers have usually modi ed the classical continuum mechanics to capture the small-scale effect through three different paths: the nonlocal stress gradient model 1 − e 0 a 2 ∇ 2 σ ij = σ ij [7], the strain gradient model σ ij = 1 − e 0 a 2 ∇ 2 ε ij [9,[25][26], and the surface stress model [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures made of temperature-dependent functionally graded materials (FGMs) have played a key role in the advancement of nanotechnologies for the design of devices such as nanoswitches, nanosensors, nanoactuators, and nanogenerators, as well as nanoelectromechanical systems (NEMS), for use even under extreme temperature and humidity conditions [1][2][3][4][5][6][7][8]. Recent studies have also shown that, by managing some fabrication parameters during the manufacture of FGMs, different kinds of porosity distributions can be obtained within their structure to further improve the physical and mechanical characteristics of the material [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This hindrance is particularly noticeable when dealing with single-walled carbon nanotubes (SWNTs), which are expected to show nontrivial correlation between mechanical deformation and their physical properties [ 9 , 10 ]. This may be a reason why tremendous efforts based on numerical simulations [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and continuum approximation theory [ 11 , 17 , 19 , 20 , 21 , 22 ] have been exerted in exploring the buckling behavior of SWNTs under loading. Several theoretical studies have revealed that axial buckling of SWNTs is highly dependent on the lattice irregularity [ 23 , 24 ] and tube chirality [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%